1980
DOI: 10.1111/j.1365-3180.1980.tb00061.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of glyphosate on the development and cell infrastructure of white mustard (Sinapis alba L.) seedlings

Abstract: Summary: The phytotoxicity of glyphosate(N‐(phosphonomethyl glycine) to seedlings of white mustard (Sinapis alba) cultivated indoors was studied. Yellowing and wrinkling of leaves was observed, necrotic spots appeared and the elongation of the seedlings was significantly reduced at doses 0–49 kg ai/ha and above. Only when sprayed at 4–97 kg ai/ha was the effect of glyphosate 100% lethal (5–7 days after spraying) At the highest concentration of herbicide a marked decrease in chlorophyll content was found but wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

1982
1982
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 10 publications
2
5
0
Order By: Relevance
“…From the current work, male reproductive organs in GR cotton appear to be only partially resistant to the effects of glyphosate, presumably because of the insufficient presence of CP4-EPSPS. However, affected pollen does not seem to degenerate as has been reported for chloroplasts in glyphosate-treated plants (Mollenhauer et al 1987;Uotila et al 1980). Membranes are intact, and no unusual organelle swelling is observed, except for the distended ER.…”
Section: Cp4-epsps In Tissuessupporting
confidence: 58%
See 2 more Smart Citations
“…From the current work, male reproductive organs in GR cotton appear to be only partially resistant to the effects of glyphosate, presumably because of the insufficient presence of CP4-EPSPS. However, affected pollen does not seem to degenerate as has been reported for chloroplasts in glyphosate-treated plants (Mollenhauer et al 1987;Uotila et al 1980). Membranes are intact, and no unusual organelle swelling is observed, except for the distended ER.…”
Section: Cp4-epsps In Tissuessupporting
confidence: 58%
“…Glyphosate has previously been shown to affect plastid integrity by causing plastids to swell or burst (Mollenhauer et al 1987;Uotila et al 1980) or to have abnormal chloroplast grana (Pihakaski S. and Pihakaski K. 1980;Vaughn and Duke 1986). Other cellular organelles are likewise sen-sitive to glyphosate disruption.…”
Section: Glyphosate Effects On Pollen Morphologymentioning
confidence: 99%
See 1 more Smart Citation
“…Both glyphosate treatments caused inwardly progressing chlorosis of leaf disc borders ( Fig. 2A, right), a wellknown effect of glyphosate (Uotila et al, 1980;PlineSrnic, 2005). The effect was stronger in treatment HG compared with treatment LG.…”
Section: Diel Growth Cyclementioning
confidence: 85%
“…1 are not necessarily evidence that this herbicide acts as a photosynthetic electron transport inhibitor, since Campbell et al (1976) reported ultrastruetural damage to plastids of qwackgrass mesophyll cells as early as 24 h after glyphosate treatment. Uotila et at. (1980) also reported that mustard chloroplasts showed swelling and an increase in plastoglobuli which were not observed in the control cells.…”
Section: Discussionmentioning
confidence: 99%